Pancreatic cancer risk and ABO blood group alleles: results from the pancreatic cancer cohort consortium. - Wolpin, B; Kraft, P; Gross, M; Helzlsouer, K; Bueno-de-Mesquita, H; Steplowski, E; Stolzenberg-Solomon, R; Arslan, A; Jacobs, E; Lacroix, A; Petersen, G; Zheng, W; et al. (2010)
A recent genome-wide association study (PanScan) identified significant associations at the ABO gene locus with risk of pancreatic cancer, but the influence of specific ABO genotypes remains unknown. We determined ABO genotypes (OO, AO, AA, AB, BO, and BB) in 1,534 cases and 1,583 controls from 12 prospective cohorts in PanScan, grouping participants by genotype-derived serologic blood type (O, A, AB, and B). Adjusted odds ratios (ORs) for pancreatic cancer by ABO alleles were calculated using logistic regression. Compared with blood type O, the ORs for pancreatic cancer in subjects with types A, AB, and B were 1.38 [95% confidence interval (95% CI), 1.18-1.62], 1.47 (95% CI, 1.07-2.02), and 1.53 (95% CI, 1.21-1.92), respectively. The incidence rates for blood types O, A, AB, and B were 28.9, 39.9, 41.8, and 44.5 cases per 100,000 subjects per year. An increase in risk was noted with the addition of each non-O allele. Compared with OO genotype, subjects with AO and AA genotype had ORs of 1.33 (95% CI, 1.13-1.58) and 1.61 (95% CI, 1.22-2.18), whereas subjects with BO and BB genotypes had ORs of 1.45 (95% CI, 1.14-1.85) and 2.42 (1.28-4.57). The population attributable fraction for non-O blood type was 19.5%. In a joint model with smoking, current smokers with non-O blood type had an adjusted OR of 2.68 (95% CI, 2.03-3.54) compared with nonsmokers of blood type O. We concluded that ABO genotypes were significantly associated with pancreatic cancer risk.